Tecnologías de conservación de filetes de pescado fresco - Martínez Layza, Ronal Tito (2017)
In the present research it has been conducted a thorough review of the latest research on key technologies applied in the conservation of fresh fish fillets because we know that fish is an important source of high quality protein, however, it is more susceptible to microbiological and chemical deterioration, due to their high water activity, neutral pH, relatively large amounts of free amino acids, and the presence of autolytic enzymes that make it very perishable. This with leads to the use of alternative methods for preserving ranging from a cold chain that does not control all alterantes reactions, so that the use of antioxidants, antimicrobials, use of barriers against external factors is necessary as they are vacuumed , modified atmosphere, food packaging (coating), active packaging, applications salted, smoked, magnetic radiation, among others, which in combination between these is achieved one goal is the conservation of fresh fish fillets, extending the life useful and maintaining almost all its physical and chemical properties. Therefore it was noted with interest research of novel methods for energy using products of plant origin, such as microbial that could provide avenues for the future in the context of improving the quality of acceptance of the fish fillets so they can reach food more people who for reasons of their rapid deterioration not consumed in remote areas of the production centers